Friction and Wear Studies Using Taguchi Method: Application to the Characterization of Carbon-Silicon Carbide Tribological Couples of Automotive Water Pump Seals - Pascal Déprez; Philippe Hivart; Jean François Coutouly; Etienne Debarre (Advances in Materials Science and Engineering)
An experimental design based on the Taguchi method has been applied to optimize the use of a dynamic sealing element of water pump of automotives combustion engines. A carbon primary ring and a silicon carbide mating ring set up this dynamic sealing element. The aim of this work was to experimentally determine the crossed influence of the primary ring variant, the normal load, the surrounding, the mating ring finishing, and the rotational frequency on the dynamic friction coefficient and on the wear of carbon primary ring-silicon carbide mating ring tribological couples. The coefficient of dynamic friction and the wear depend on the design factors. They are also functions of the interactions between these experimental factors, from the implementation of an experimental design. The results obtained allow the optimal functioning condition to be determined and the best friction couple to be used for a given dynamic sealing application.